Multimodal computed tomography of the brain - ธรรมสโรช พรภัทร (Journal of Thai Stroke Society, 2019)
Multimodal computed tomography comprised of noncontrast- enhanced computed tomography (NECT), perfusion computed tomography (CTP) and computed tomography angiography (CTA) has been increasingly used in research and clinical practice. CTP provides information about cerebral blood flow status. CTP parameters consist of cerebral blood volume (CBV), cerebral blood flow (CBF) and mean transit time (MTT). By gathering data from CTP parameters, penumbra and core infarct might be predicted. CTA provides information about vessel status, which may help in making decision about choices of treatment, such as intravenous thrombolysis or endovascular treatment, in patients with acute ischemic stroke